Differentiated therapy in pre- and postmenopausal adnexal torsion based on malignancy rates: A retrospective multicentre study over five years. (May 2016) - Ozcan, Aykut; Mumusoglu, Sezcan; Gokcu, Mehmet; Caypinar, Sema Süzen; Sagiroglu, Cengiz; Inan, Abdurrahman Hamdi; Aktoz, Fatih; Biler, Alper; Turan, Volkan; Töz, Emrah; Ozdemir, Isa Aykut; Bozdag, Gurkan
Abstract: Introduction: The purpose of this study was to investigate the clinical presentation, intra and postoperative outcomes in pre and postmenopausal women who underwent operations for adnexal torsion, and to define our experience diagnosing and managing postmenopausal women with adnexal torsion. Methods: One hundred and fifty-seven patients who underwent operation with a diagnosis of adnexal torsion were analyzed according to demographic characteristics, menopausal status, preoperative signs and symptoms, surgical findings and applied surgical procedures, and pathological results in four tertiary centers. Results: The main indication for surgery for the postmenopausal women was pelvic mass (58% vs. 40%), while for premenopausal women the main indication was suspicion of torsion (55% vs. 24%), (each p < 0.001). The duration of time between being admitted to the hospital and entering operating room as well as the duration of surgery and postoperative hospitalization were statistically longer in the postmenopausal group (each p < 0.001). While extensive surgeries were performed for 68% of the postmenopausal group, this was required for only 3% of the premenopausal group. Functional cysts were the most common pathologic finding in premenopausal women, and only 2 cases of malignancy (1.6%) were seen as opposed to the postmenopausal group, where malignancy was diagnosed in 16% of cases (p < 0.001). Discussion: Adnexal torsion in postmenopausal women is an uncommon event. Malignancy risk should be considered before operation. Conclusion: The malignancy rate was 16% in postmenopausal women with adnexal torsion. Thus, extensive surgeries are more common in postmenopausal women with adnexal torsion. Highlights: Adnexal torsion (AT) is a rarely seen event in postmenopausal women. The malignancy rate in postmenopausal women accounts for 16% of all cases with AT. The management of AT should be different between pre and postmenopausal women.